Association between controlling nutritional status score and the prognosis of patients with heart failure: a systematic review and meta-analysis - Yuan, Yuan; Wang, Su-Ping; Guan, Yi; Yang, Qing-Yi; Zhong, Peng-Yu; Wang, Hao-Yu (Frontiers in Cardiovascular Medicine, 2025)
BackgroundMalnutrition frequently complicates heart failure (HF), interacting with systemic inflammation, metabolic dysregulation, and immune dysfunction to accelerate disease progression. The Controlling Nutritional Status (CONUT) score, derived from objective laboratory parameters (serum albumin, total cholesterol, lymphocyte count), quantifies nutritional derangements and has emerged as a promising tool for HF risk stratification and prognostic prediction. However, accumulating evidence requires systematic synthesis to establish its clinical validity.MethodsA comprehensive literature search was conducted in databases including PubMed, Embase, the Cochrane Library and Web of Science, covering all available records up to January 27, 2025, to identify research examining the association between the CONUT score and HF outcomes.ResultsThe analysis included 28 cohort studies. Pooled data demonstrated a significant correlation between elevated CONUT scores and higher rates of all-cause mortality (HR = 1.57, 95% CI 1.35–1.83; P < 0.00001). Despite substantial heterogeneity, sequential exclusion sensitivity analyses confirmed the robustness of this association, with recalculated estimates consistently showing overlapping confidence intervals across all analytical scenarios.ConclusionBased on the definition of the CONUT score, malnutrition remains a significant factor associated with overall mortality risk in individuals diagnosed with heart failure, even after controlling for potential confounders. Utilizing the CONUT score for nutritional assessment enables clinicians to detect patients who are more likely to experience unfavorable clinical outcomes.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251023217, PROSPERO CRD420251023217.